Literasi Kesehatan terhadap Penerapan Pola Makan 3J Pasien Diabetes Melitus - Dwi Aguatina; Ulfa Alfianti; Kamilia Utami (Universitas Malahayati Lampung, 2025)
ABSTRACT Diabetes Mellitus (DM) is a significant global health threat, with its prevalence increasing, particularly in developing countries like Indonesia. Effective blood glucose management is essential to prevent complications, and this can be achieved through the implementation of the 3J eating pattern (type, timing, and portion). Health literacy plays a crucial role in enabling patients to adopt the 3J eating pattern properly. This study aims to analyze the relationship between health literacy and the implementation of the 3J eating pattern in patients with Diabetes Mellitus. A quantitative cross-sectional design was employed, using univariate frequency distribution analysis and bivariate chi-square analysis. The research was conducted at Kelapa Dua Wetan Public Health Center, Ciracas, with 70 respondents selected through purposive sampling. The independent variable was health literacy, while the dependent variable was the 3J eating pattern. The univariate analysis showed that 74.29% of respondents had moderate health literacy, and 74.29% demonstrated a moderate implementation of the 3J eating pattern. The bivariate analysis revealed a significant relationship between health literacy and the 3J eating pattern, with a p-value of 0.000. There is a significant relationship between health literacy and the implementation of the 3J eating pattern in Diabetes Mellitus patients. Improving health literacy can enhance patients' ability to manage their diet effectively, ultimately helping maintain normal blood glucose levels and prevent complications. Keywords: Health Literacy, 3J Eating Pattern, Diabetes Mellitus, Blood Glucose Management ABSTRAK Diabetes Melitus (DM) merupakan penyakit kronis yang menyebabkan komplikasi berbagai organ tubuh. Pencegahan komplikasi DM dapat dicapai dengan memastikan kadar gula dalam darah normal. Salah satu Upaya menormalkan gula dalam darah adalah dengan mengatur pola makan 3J. Literasi Kesehatan baik membuat pasien mampu mengatur pola makan 3J dengan baik. Penelitian ini untuk menganalisis antara literasi Kesehatan dengan pola makan pasien DM.Design penelitian kuantitatif cross sectional dengan analisa univariat distribusi frekuensi dan analisa bivariat chi-square. Penelitian dilakukan di Puskesmas Kelapa Dua Wetan, Ciracas. Variabel independent pada penelitian ini adalah literasi kesehatan sedangkan dependen adalah penerapan pola makan 3J. Hasil data penelitian univariat literasi kesehatan pada klasifikasi cukup (74.29%) dan pola makan 3J pada klasifikasi cukup (74.29%). Hasil penelitian bivariat didapatkan hasil pvalue 0.000. Terdapat hubungan signifikan antara literasi kesehatan dengan pola makan 3J pada pasien DM. Kata Kunci: Literasi Kesehatan, Pola Makan 3J, Diabetes Melitus.